A case of laparoscopic high anterior resection of rectosigmoid colon cancer associated with a horseshoe kidney using preoperative 3D-CT angiography - Naoki Kubo; Norihiko Furusawa; Shinichiro Imai; Masaru Terada (Surgical Case Reports)
Abstract Background Horseshoe kidney is a congenital malformation in which the bilateral kidneys are fused. It is frequently complicated by other congenital malformations and is often accompanied by anomalies of the ureteropelvic and vascular systems, which must be evaluated to avoid iatrogenic injury. We report a case of laparoscopic high anterior resection of rectosigmoid colon cancer associated with a horseshoe kidney using preoperative 3D-CT angiography. Case presentation A 52-year-old Japanese man with lower abdominal pain underwent lower endoscopy, revealing a type 2 lesion in the rectosigmoid colon. He was diagnosed with rectosigmoid colon cancer with multiple lung metastases and a horseshoe kidney on computed tomography (CT) scan. Three-dimensional (3D)-CT angiography showed an aberrant renal artery at the isthmus from 3 cm under the inferior mesenteric artery (IMA) branch of the aorta. Laparoscopic anterior rectal resection was performed. During the operation, the inferior mesenteric artery, left ureter, left gonadal vessels, and hypogastric nerve plexus could be seen passing over the horseshoe kidney isthmus and were preserved. The left branch of aberrant renal artery that was close to IMA was also detected and preserved. Conclusion To prevent intraoperative misidentification, 3D-CT angiography should be performed preoperatively to ascertain the precise positional relationships between the extra renal arteries and the kidney. We always must consider anomalous locations of renal vessels, ureter, gonadal vessels, and lumbar splanchnic nerve to avoid laparoscopic iatrogenic injury in patients with a horseshoe kidney.